PENINGKATAN GOOD GOVERNANCE DAN MEMBANGUN TEAM BUILDING PADA SEKOLAH LITTLE BEE HOUSE PAMULANG - Listya Sugiyarti; Siti Hanah; Nur Asmilia; Effriyanti Effriyanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The purpose of this Community Service activity is to provide insight into good governance and build team building spirit for teachers, management and the school community. In this Community Service activity, counseling, mentoring and training methods are used with a service learning approach through material presentations, group discussions, question and answer, role play and team games that are relevant to the theme. Feedback from service activities by filling out questionnaires from participants. The result of the service activities is that Good Governance in the Little Bee House school is very important because it is a solid and responsible school administration process, as well as efficient and effective by maintaining a synergistic constructive interaction between various institutional and community resources. Team Building is an activity that is needed in building a reliable team such as good cooperation among team members to achieve predetermined targets and improving teamwork operations in the Little Bee House school environment. A combination of training and games to train team building to achieve a solid, responsive, focused team and achieve team goals in achieving the vision and mission targets. The output of the PkM results to the participants is that the implementation of the nine characteristics of good governance in schools is not solely based on the call for professionalism of school personnel, but rather on the internal and external demands of the school. implementers, school committees play a role in supporting resources, supervising, giving consideration, and intermediaries. The vision carried out by team building must be strong between the leadership and team members.